Bureaucracies Under Judicial Control? Relational Discretion in the Implementation of Immigration Detention in Swiss Cantons - Miaz, Jonathan; Achermann, Christin (My University, 2021)
Based on interviews with bureaucrats and judges in several Swiss cantons, this article analyzes how bureaucrats decide to order immigration detention and how the judicial review shapes their decisions. The authors argue that discretionary decision-making regarding immigration detention is structured by the web of relationships in which decision-makers are embedded and affected by the practices of other street-level actors. The varying cantonal configurations result in heterogenous bureaucratic practices that affect the profiles and numbers of persons being detained. In particular, differences in judges’ interpretation of legal principles, as well as in their expectations, strongly affect bureaucratic decisions.
Keywords: immigration detention; street-level bureaucracy; courts; discretion; legal decision-making; judicial review; federalism; Switzerland